Good library manners for a better library - Singapore. National Library Board (Singapore The Board, 1999)
Provides an overview of Singapore libraries' state-of-the-art offerings as well as the personalised services still available and associated with the "traditional" library. It also features the importance of library manners.
VCD.
Keywords: Library orientation -- Singapore; Library orientation -- Computer-aided instruction